Clinical effectiveness and cost-effectiveness of physiotherapy and occupational therapy versus no therapy in mild to moderate Parkinson’s disease: a large pragmatic randomised controlled trial (PD REHAB) - Clarke, Carl E.; Patel, Smitaa; Ives, Natalie; Rick, Caroline E.; Woolley, Rebecca; Wheatley, Keith; Walker, Marion F.; Zhu, Shihua; Kandiyali, Rebecca; Yao, Guiqing; Sackley, Catherine M. (NIHR Health Technology Assessment Programme, 2016)
Background